Integration of Metabolomics and Transcriptomics to Reveal the Antitumor Mechanism of Dendrobium officinale Polysaccharide-Based Nanocarriers in Enhancing Photodynamic Immunotherapy in Colorectal Cancer - Shengchang Tao; Huan Wang; Qiufeng Ji; Yushan Yang; Gang Wei; Ruiming Li; Benjie Zhou (Pharmaceutics)
Background: The mechanism of Dendrobium officinale polysaccharide-based nanocarriers in enhancing photodynamic immunotherapy in colorectal cancer (CRC) remains poorly understood. Methods: The effects of TPA-3BCP-loaded cholesteryl hemisuccinate–Dendrobium officinale polysaccharide nanoparticles (DOP@3BCP NPs) and their potential molecular mechanism of action in a tumor-bearing mouse model of CRC were investigated using non-targeted metabolomics and transcriptomics. Meanwhile, a histopathological analysis (H&E staining, Ki67 staining, and TUNEL assay) and a qRT-PCR analysis revealed the antitumor effects of DOP@3BCP NPs with and without light activation. Results: Through metabolomics and transcriptomics analysis, we found an alteration in the metabolome and functional pathways in the examined tumor tissues. The metabolic analysis showed 69 and 60 differentially expressed metabolites (DEMs) in positive- and negative-ion modes, respectively, in the treated samples compared to the Control samples. The transcriptomics analysis showed that 1352 genes were differentially expressed among the three groups. The differentially regulated functional pathways were primally related to the antitumor immune response. The results of the pathological histology assay and qRT-PCR analysis verified the findings of the integrated metabolomics and transcriptomics analysis. Conclusions: Overall, our findings elucidate the potential antitumor mechanisms of the D. officinale polysaccharide-based nanocarrier in enhancing photodynamic immunotherapy in CRC.